2002
DOI: 10.1096/fj.02-0187fje
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of tumor necrosis factor α in traumatic muscle injury

Abstract: degenerative and regenerative roles of tumor necrosis factor alpha (TNF-alpha), a pro-inflammatory cytokine with pleiotropic functions, were investigated by using TNF receptor 1 and 2 double knockout (TNFR-DKO) and TNF-alpha antibody neutralized mice following traumatic freeze injury to the tibialis anterior muscle. In wild-type control mice, TNF-alpha mRNA transcripts and protein increased following injury and gradually returned to control (uninjured) levels by 13 days. A reduction in MyoD mRNA expression occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
208
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(227 citation statements)
references
References 39 publications
14
208
2
3
Order By: Relevance
“…Following muscle injury, the early invading neutrophil and macrophage populations express TNF-␣ (15,137), suggesting that the cytokine may contribute to the early inflammatory stages that precede muscle regeneration. TNF-␣ levels in muscle following acute injury peak at 24 h postinjury, which indicates that TNF-␣ production is most tightly coupled with the Th1 inflammatory response in injured muscle (126). Because findings show that TNF-␣ induces iNOS in myeloid cells and that myeloid cell-derived NO can cause muscle fiber damage that occurs during the early, Th1 inflammatory response following muscle injury, TNF-␣ activation of inflammatory cells has been associated with promoting muscle damage.…”
Section: Do Neutrophil-derived or M1 Macrophage-derived Molecules Modmentioning
confidence: 77%
“…Following muscle injury, the early invading neutrophil and macrophage populations express TNF-␣ (15,137), suggesting that the cytokine may contribute to the early inflammatory stages that precede muscle regeneration. TNF-␣ levels in muscle following acute injury peak at 24 h postinjury, which indicates that TNF-␣ production is most tightly coupled with the Th1 inflammatory response in injured muscle (126). Because findings show that TNF-␣ induces iNOS in myeloid cells and that myeloid cell-derived NO can cause muscle fiber damage that occurs during the early, Th1 inflammatory response following muscle injury, TNF-␣ activation of inflammatory cells has been associated with promoting muscle damage.…”
Section: Do Neutrophil-derived or M1 Macrophage-derived Molecules Modmentioning
confidence: 77%
“…1). It is important to note that although this in vivo model measures isometric torque produced by the left anterior crural muscles, the TA comprises 82 % of the muscle group mass and contributes 89 % of the peak torque produced by the muscle group making it a valid assessment of TA muscle function (Lowe et al 1995;Warren et al 2002).…”
Section: Experimental Designmentioning
confidence: 99%
“…Two days or more after injury, the levels had normalized. Similarly, Warren et al 8. reported that traumatic skeletal muscle injury is accompanied by an early increase in TNF‐α expression characterized by a single peak that is maximal at 24 hours after injury, as seen using real‐time polymerase chain reaction.…”
Section: Discussionmentioning
confidence: 87%
“…The invasive freeze‐induced model8 and contraction‐induced model of muscle injury9 are well known. However, these models do not closely match clinical observations.…”
mentioning
confidence: 99%
See 1 more Smart Citation